Sabine Lippert's beadwork evolution : new techniques using peyote stitch and right angle weave - Lippert, Sabine, 1967- (Lark jewelry & beading., 2014)
"The book features 25 how-to instructions plus illustrations on making advanced jewelry designs in peyote stitch and right angle weave, the two most popular stitches. The book is aimed at intermediate and advanced beaders, as well as ambitious beginners--the aspirational and inspiration-seeking audience"--